RELATIONSHIPS BETWEEN PERSONALITY TRAITS, LIFESTYLES AND ACADEMIC ACHIEVEMENT OF STUDENTS - Snježana Stanar; Nevena Pejić (STED Journal)
The term "lifestyle" is a central concept of Adler's theory of personality, which he defines as a characteristic pattern of behavior that is a manifestation of a unique way of perceiving, conceptualizing, behaving and personal striving towards a goal that is filled with subjective meaning and represents part of the striving for power (Croake, 1975). Personality traits represent dimensions of individual differences that relate to a person's tendency to exhibit consistent patterns of thought, feeling, and action (McCrae & Costa, 1985). The research sample consisted of a total of 211 respondents, mostly students of the University of East Sarajevo surveyed via online questionnaires, of which 135 were female and 76 were male. Measuring instruments with satisfactory measurement characteristics were used: Questionnaire for examining the Big Five personality model (Goldberg, 1992), a modified version of the Allport-Vernon-Lindzis value scale for measuring lifestyles, a Scale for examining the sociodemographic characteristics of the respondents, and a Scale for examining academic performance. The obtained data show that of all personality dimensions of the Big Five model, only conscientiousness has a statistically significantly positive correlation with achieved academic success expressed through the average grade in studies (r=.24), which is not surprising, because this is a trait that is consistently associated with academic and business success in a large number of studies. Four lifestyle styles statistically significantly correlate with achieved academic success: family-sentimental style (r=.15), cognitive style (r=0.16), popularity-oriented style (r=-.19) and Promethean activism (r=.15). Although none of the mentioned correlations are high, they indicate the undoubted existence of a connection between these constructs and the role that lifestyles as complex systems of values, goals, attitudes and beliefs play in determining the final forms of behavior and achieved results within the educational system.